Grayscale Morphological Analysis Of DNA Microarray For Spot Classification - Latha, Behara (2004)
DNA microarray image analysis is an important topic from the point of view of bioinformatics. A microarray consisting of several spots with varied gene expression levels is a grey level image. This study provides a simple framework to classify microarray spots based upon their gene expression levels. This work demonstrates possibility to unravel topological characteristics of microarrays using powerful computers and established tools like mathematical morphology. These characteristics provide new insights in understanding microbiological phenomena in a quantitative manner. In this study we provide a simple but elegant framework, based on mathematical morphology, to unravel various morphological characteristics of microarray spots.